2008
DOI: 10.1037/0008-400x.40.1.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Looking within: Measuring state self-forgiveness and its relationship to psychological well-being.

Abstract: Although considerable empirieal attention has recently focused on forgiveness, less work has been done on examining self-forgiveness, A major stumbling block for self-forgiveness research has been the lack of a measure to assess self-forgiveness for specific transgressions. This article reports the development of the State Self-Forgiveness Scales and the test of a model of self-forgiveness' relation to psychological well-being in the context of the unwanted end of a romantic relationship. In Study 1, factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
167
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(189 citation statements)
references
References 37 publications
8
167
1
13
Order By: Relevance
“…La ausencia o dificultad de ejercer perdón sobre uno mismo está asociado a niveles altos de psicopatología (Hall y Fincham, 2005;Ross et al, 2004), depresión o ansiedad (e.g., Romero et al, 2006;Wohl et al, 2008) y disminución de la satisfacción general con la vida (Thompson et al, 2005). En contraposición, perdonarse se relaciona con salud mental y bienestar incluso de forma más intensa que el perdón a los demás (Mauger et al, 1992;Thompson et al, 2005).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La ausencia o dificultad de ejercer perdón sobre uno mismo está asociado a niveles altos de psicopatología (Hall y Fincham, 2005;Ross et al, 2004), depresión o ansiedad (e.g., Romero et al, 2006;Wohl et al, 2008) y disminución de la satisfacción general con la vida (Thompson et al, 2005). En contraposición, perdonarse se relaciona con salud mental y bienestar incluso de forma más intensa que el perdón a los demás (Mauger et al, 1992;Thompson et al, 2005).…”
Section: Discussionunclassified
“…Distintos estudios muestran indicadores de la relevancia del autoperdón para la salud mental. Se ha relacionado el perdón disposicional a uno mismo con una alta autoestima (Hall y Fincham, 2005;Mauger et al, 1992), satisfacción con la vida (Hall y Fincham, 2005) y bienestar psicológico (Jacinto, 2010;Wohl, DeShea y Wahkinney, 2008). Asimismo, el fracaso para perdonarse predice baja autoestima (Mauger et al, 1992) y altos niveles de culpa (Zechmeister y Romero, 2002).…”
unclassified
See 1 more Smart Citation
“…La primaria busca entender lo que es el evento y lo que significa (Taylor, 2015), y frente a cualquier transgresión puede implicar identificar que la situación ha generado un daño o pérdida, una amenaza, o un desafío (Strelan y Covic, 2006). En el caso de una ofensa a sí mismo, este proceso implica el reconocimiento de haber cometido un error (Wohl, DeShea y Wahkinney, 2008), que no necesariamente es una conducta externa sino que puede ser pensamientos, sentimientos o deseos percibidos como dañinos (Hall y Fincham, 2005). Esta evaluación también puede permitir percibir el hecho como no ofensivo, siendo en este caso una situación irrelevante para perdonar, pues "falta es la presuposición existencial del perdón" (Casullo, 2005, p. 44).…”
Section: Evaluaciónunclassified
“…Several studies have shown the associations of self-forgiveness to depression and anxiety, and the effect of self-forgiveness on psychological well-being, through a onedimensional self-forgiveness (i.e., considering higher scores of the self-forgiveness scale as forgiveness and considering lower scores of the self-forgiveness scale as a failure to forgive; Maltby et al, 2001;Mauger et al, 1992;Wohl et al, 2008) but not through the process-oriented approach of self-forgiveness. The study of Woodyatt and Wenzel (2013b) indicated that offenders' greater perception of belongingness and lower levels of feelings of rejection from others may reduce the defensive attitudes of pseudo selfforgiveness, which, in turn, facilitates genuine self-forgiveness.…”
Section: Current Study and Hypothesesmentioning
confidence: 99%